Education and female migrants in transit in Mexico’s northern border. Education as a variable and future expectation in the migration process - Teresa Terrón-Caro (Revista Complutense de Educación, 2018)
Education is one of the most important elements for the development in societies. In Mexico and Central America, where the vast majority of non-authorized immigrants in the United States come from, equal opportunities in access —and permanence— to the education system remains a pending issue. For this reason, educational achievements, as well as material improvement, are very important aspects in the “American Dream” for the population that wants to reach that country, and particularly for the migrant women in our study In the next article, we present the results of a qualitative investigation carried out in the northern border of Mexico with the USA. In which we analyzed the educational expectations from the women in their migration project, and how education plays as an important variable in the preparation for their trip and also in the minimization of risks during their trip. Thru in-depth interviews, we make a qualitative analysis on the motivations that lead these women to start their journey and the resources they have for tackling the risks, where education plays a role in both cases. In the findings, we can say that the formal education received in their place of origin, conditions the migration project of non-documented migrant women traveling to the US: their scope, their travel strategy, as well as their responses to danger. And in the same manner, the educational achievement, for themselves or their dependents, as part of their migration project. In this scenario, the notion of return does not allow them, in some cases, to fulfill their expectations of the “American Dream”.